Geochronology and Petrogenesis of Hadean to Paleoarchean Mafic and Felsic Crust from the Northeastern Superior Province, Canada - Sole, Christian (Université d'Ottawa / University of Ottawa, 2021)
The first billion years of our planet’s history is almost devoid of geological records and this scarcity of Eoarchean/Hadean rocks and minerals greatly limits our understanding of how and when the first crust formed on Earth. The Nuvvuagittuq Greenstone Belt (NGB), located in the Hudson Bay terrane of the Northeastern Superior Province, may host the oldest preserved rocks on Earth. It is locally intruded in its southwestern corner by rare 3.76 Ga trondhjemite bands which impose a minimum age for the NGB, but its dominant lithology, a mafic cummingtonite-amphibolite called the Ujaraaluk unit, displays isotopic evidence suggesting it may represent a rare remnant of Hadean mafic crust as old as 4.3 Ga. However, this proposed Hadean age for the NGB has been heavily debated for more than a decade. As potentially the only remnant of crust formed within the first 500 million years of Earth’s history, the NGB could have important implications on our knowledge of the first terrestrial crust. In order to impose tighter geochronological constraints on the NGB, here we present U-Pb zircon and ¹⁴⁷Sm-¹⁴³Nd whole rock data for gneissic gabbro sills that intrude the Ujaraaluk unit as well as U-Pb data for zircons from intruding and surrounding granitoids. A new strategy of sampling for the gneissic gabbros targeted the most evolved plagioclase-rich zones and amphibole-rich cumulative rocks to better constrain their age of magmatic differentiation. The most evolved parts of the sills were also sampled because they are the most likely to contain igneous zircon or baddeleyite that could constrain their crystallization age. Zircons from two compositionally evolved gneissic gabbros yielded U-Pb ages between 2.7 and 2.6 Ga consistent with the timing of Neoarchean metamorphism in the region. A plagioclase-rich layer found within the gabbro sills yielded zircons defining a U-Pb Concordia upper intercept age of 2789 Ma, but their texture and Th/U ratios are more consistent with recrystallization of zircon subsequent to the breakdown of an older Zr-bearing phase and therefore do not constrain the age of emplacement of the sills. However, a ¹⁴⁷Sm-¹⁴³Nd isochron for the gneissic gabbros, including the newly identified plagioclase-rich evolved zone and hornblende-rich cumulative rock, yielded an isochron age of 4151 ± 290 (MSWD = 9, n = 6) interpreted as the timing of magmatic differentiation of the sills. This 4.1 Ga age thus strongly supports the previously proposed Hadean age for the NGB. New zircon U-Pb data reported here for plutonic trondhjemites found in the central and eastern parts surrounding the NGB suggests that the extent of the ~3.8 Ga Eoarchean felsic magmatism is greater than previously thought. New zircon trace element and oxygen isotope data for a series of granitoids surrounding and locally intruding the NGB previously dated at 3.76 Ga, 3.66 Ga, 3.51 Ga and 3.35 Ga provide a better understanding of the petrogenetic processes responsible for early felsic crust production. Zircons from the 3.76 Ga, 3.66 Ga and 3.35 Ga granitoids are characterized by rare earth element trends typical of unaltered igneous zircons. However, zircons from the 3.51 Ga magmatic event display unusual rare earth element patterns, with a striking positive Eu-anomaly, suggesting that they may have experienced some type of post-magmatic alteration. Zircon δ¹⁸O values appear to have slightly increased over time with the zircons from the oldest 3.76 Ga trondhjemites displaying mean δ¹⁸O values within the mantle zircon field and the younger Paleoarchean granitoids progressively deviating from the mantle zircon field to reach a mean zircon δ¹⁸O value of 6.58‰ at 3.35 Ga. This suggests that the 3.76 Ga trondhjemites were derived from an unaltered crustal source, whereas the ≤3.66 Ga granitoids were derived from a supracrustal source that had experienced some degree of low-temperature hydrothermal alteration. This trend of mantle-like zircon δ¹⁸O values preserved in the first evolved crust, which deviate towards higher zircon δ¹⁸O values in successive felsic magmatic events, has also been observed in other Hadean and Eoarchean terranes indicating that similar processes may have operated on a global scale during the production and evolution of early continental crust.
Keywords: Geochronology; Nuvvuagittuq; Hadean; Crust